2020
DOI: 10.1007/s12035-020-01868-8
|View full text |Cite
|
Sign up to set email alerts
|

Selected microRNAs Increase Synaptic Resilience to the Damaging Binding of the Alzheimer’s Disease Amyloid Beta Oligomers

Abstract: Alzheimer's disease (AD) is marked by synaptic loss (at early stages) and neuronal death (at late stages). Amyloid beta (Aβ) and tau oligomers can target and disrupt synapses thus driving cognitive decay. Non-demented individuals with Alzheimer's neuropathology (NDAN) are capable of withstanding Aβ and tau toxicity, thus remaining cognitively intact despite presence of AD neuropathology. Understanding the involved mechanism(s) would lead to development of novel effective therapeutic strategies aimed at promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…Numerous studies in recent decades have focused on elucidating the etiopathology of AD, but its pathogenesis remains unclear, and no therapeutic strategy is available to cure this disease. Various molecular, biochemical, and cellular abnormalities such as cell loss, impaired energy metabolism, increased activation of signaling pathways, amyloid-β (Aβ) deposits, mitochondrial dysfunction, chronic oxidative stress, impaired energy metabolism, and DNA damage are involved in the pathogenesis of AD (Guo et al, 2020;Zhang Y. X. et al, 2020;Zolochevska and Taglialatela, 2020;Ashford et al, 2021). The neuropathological hallmarks of AD include the formation of senile plaques and neurofibrillary tangles in specific brain regions that lead to synaptic loss and neuronal death (Khan and Hegde, 2020;Mattsson-Carlgren et al, 2020;Konijnenberg et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies in recent decades have focused on elucidating the etiopathology of AD, but its pathogenesis remains unclear, and no therapeutic strategy is available to cure this disease. Various molecular, biochemical, and cellular abnormalities such as cell loss, impaired energy metabolism, increased activation of signaling pathways, amyloid-β (Aβ) deposits, mitochondrial dysfunction, chronic oxidative stress, impaired energy metabolism, and DNA damage are involved in the pathogenesis of AD (Guo et al, 2020;Zhang Y. X. et al, 2020;Zolochevska and Taglialatela, 2020;Ashford et al, 2021). The neuropathological hallmarks of AD include the formation of senile plaques and neurofibrillary tangles in specific brain regions that lead to synaptic loss and neuronal death (Khan and Hegde, 2020;Mattsson-Carlgren et al, 2020;Konijnenberg et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“… 174 A similar effect was achieved with miR-188-5p oligonucleotide transfection in 5XFAD mouse model of AD. 175 Zolochevska et al 176 used in vivo mouse model and intracerebroventricular injections to demonstrate that miR-149, miR-485 and miR-4723 could prevent Aβ oligomer binding to the synapses. The miR-200b and miR-200c mimics were also able to prevent Aβ-derived toxicity in mice.…”
Section: Potential Epigenetic Therapy For Admentioning
confidence: 99%
“…Apart from this, hippocampal injections of miR-34c inhibitors restored SIRT1 levels, a protein that contributes to memory impairment when absent [ 49 ]; intranasal delivery of the aforementioned miRNA antagomir reversed the deterioration of dendritic spines caused by β-Amyloid (Aβ) protein [ 50 ]; this was equally achieved after miR-188-5p oligonucleotide transfection into primary hippocampal neurons from 5XFAD mice [ 51 ]. Recently, Zolochevska et al [ 52 ] explored the impact of three different miRNAs (miR-149, miR-485 and miR-4723) in resilience against Aβ oligomers, which may produce synaptic dysfunction after interacting with the synapses; in vivo experiments where miRNAs were introduced via ICV injection in both male and female mice suggested that all the selected microRNAs could prevent Aβ oligomer binding. Interestingly, it was detected that target genes and RNA regulation are sex-specific.…”
Section: Alzheimer’s Disease (Ad)mentioning
confidence: 99%